A Cortázar, a palavra. - Fank, Julie (2013)
The aspects of compromise and playfulness of Julio Cortázar (1914-1984) gravitated weighing in Latin American literature of the twentieth century. Coexist in the writer inseparable critic and intellectual figures who cross the writers of the Latin American Boom called, publishing phenomenon occurred on par with Europe - a continentshelter Latin American exiles in the 60s and 70s. The evidence taken by the Belgian- Argentine-French writer among the peers appear so disparate: the positive and plural character of his experimental work, through which recognizes a strong surrealist influence and dual-critical writer a reinvention of genres; negative by (not suffered alone) contempt intellectuals who opted for intellectual escapism, or not to leave the country. In this paradoxical scenario, it is evident Cortázar as a writer, critic and intellectual who writes a book guillotined in 1969, and has called Último Round in 2009, his writings gathered in a non-descript posthumously by his biographer: Papéis Inesperados. Under the eyes of the theories of David Arirgucci Jr. (1995), Linda Hutcheon (1991), Roland Barthes (1953, 1966), Leyla Perrone-Moisés (1990, 1998, 2005) and Silviano Santiago (1982, 2002, 2004), the aim if, through the analysis of the two works, giving greater clarity to the silhouette of Julio Cortázar deed within the Latin American comparative literature, fixing a time of hybrid scriptures.